2022
DOI: 10.1155/2022/3717826
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antibacterial, and Antioxidant Activities of Thiazolyl-Pyrazoline Schiff Base Hybrids: A Combined Experimental and Computational Study

Abstract: Thiazole-pyrazoline Schiff base hybrids have a broad range of pharmacological potential with an ability to control the activity of numerous metabolic enzymes. In this work, a greener and more efficient approach has been developed to synthesize a novel series of thiazole-pyrazoline Schiff base hybrids using ZnO nanoparticle-assisted protocol in good to excellent yields (78.3–96.9%) and examined their antibacterial activity against Gram-positive and Gram-negative bacteria, as well as their antioxidant activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Thiazoles and their derivatives are extensively recognized as chemical nuclei of great interest for producing molecules with multiple biological properties [ 54 ]. In particular, several compounds bearing these heterocycles were studied for their capability to interfere with DNA topoisomerases (Topos) [ 54 , 55 , 56 ], ubiquitous enzymes essential in several key cellular processes. In recent years, these enzymes have become popular targets in cancer therapy; indeed, the topoisomerase inhibitors can induce damage to genome integrity.…”
Section: Resultsmentioning
confidence: 99%
“…Thiazoles and their derivatives are extensively recognized as chemical nuclei of great interest for producing molecules with multiple biological properties [ 54 ]. In particular, several compounds bearing these heterocycles were studied for their capability to interfere with DNA topoisomerases (Topos) [ 54 , 55 , 56 ], ubiquitous enzymes essential in several key cellular processes. In recent years, these enzymes have become popular targets in cancer therapy; indeed, the topoisomerase inhibitors can induce damage to genome integrity.…”
Section: Resultsmentioning
confidence: 99%
“…Where the following carbon atoms C 3 -C 4 -C 10 -C 22 gave values between 129.092-131.752 ppm due to the connection of carbon atoms with nitrogen atoms [23][24]. As for these two signals at 144.818-141.912 ppm, C 1 -C 2 is due to the two groups of azomethane (-C=N-) [25]. Several signals at 129.275-129.627, 129.000-129.927, and 115.742-124.927 ppm indicated the carbon atoms C 12 -C 16 , C 17 -C 21 , and C 24 -C 27 belong to the phenyls of benzil and phenol, respectively [26].…”
Section: The 13 C-nmr Spectrum Of the Ligand (Dptyeap)mentioning
confidence: 99%
“…D. Zelelew et al reported a greener synthetic methodology for a newly synthesis of thiazole-pyrazoline Schiff-base composite (194). [188] Chalcones (187) were used as the precursors for a nucleophilic cycloaddition process with hydrazine hydrate to generate intermediates of N-formyl pyrazolines (188) (Scheme 35). In the formation of chalcones derivative (191), the reaction between p-nitro acetophenone (189) and aldehyde (4) (Scheme 36).…”
Section: Synthesis Of Thiazine Thiazole and Thiophene Derivativesmentioning
confidence: 99%